Women's human rights and culture from deadlock to dialogue - Holtmaat, Riki 1952-; Naber, Jonneke M. M. 1965- (Intersentia, 2011)
In all parts of the world, the implementation of women's human rights is seriously being hindered by gender stereotypes, religion, custom or tradition, in short by 'culture'. Culture is increasingly being used as an excuse to commit serious violations of these rights. It is also brought forward as the reason why governments refuse to implement them, arguing that their culture forces them to accept limited interpretations of international obligations in this area, or to reject such obligations altogether. This book provides women's human rights advocates with dissuasive arguments and effective strategies to avoid a deadlock between on the one hand upholding the principle of universality of human rights, and on the other hand the right to preserve and express one's culture
Keywords: Convention on the Elimination of All Forms of Discrimination against Women -- 1979 Dezember 18; Menschenrecht; Kulturelle Identität; Frau